Type and extent of trans-disciplinary co-operation to improve food security, health and household environment in low and middle income countries: systematic review - Santosh Gaihre; Janet Kyle; Sean Semple; Jo Smith; Madhu Subedi; Debbi Marais (BMC, 2016)
Abstract Background Although linkages have been found between agricultural interventions and nutritional health, and the development of clean fuels and improved solid fuel stoves in reducing household air pollution and adverse health effects, the extent of the potential of combined household interventions to improve health, nutrition and the environment has not been investigated. A systematic review was conducted to identify the extent and type of community-based agricultural and household interventions aimed at improving food security, health and the household environment in low and middle income countries. Methods A systematic search of Ovid MEDLINE, PUBMED, EMBASE and SCOPUS databases was performed. Key search words were generated reflecting the "participants, interventions, comparators, outcomes and study design" approach and a comprehensive search strategy was developed following "Preferred Reporting Items for Systematic Reviews and Meta-Analyses" recommendations. Any community-based agricultural and/or household interventions were eligible for inclusion if the focus was to improve at least one of the outcome measures of interest. All relevant study designs employing any of these interventions (alone/in combination) were included if conducted in Low and middle income countries. Review articles, and clinical and occupational studies were excluded. Results A total of 123 studies were included and grouped into four intervention domains; agricultural (n = 27), air quality (n = 34), water quality (n = 32), and nutritional (n = 30). Most studies were conducted in Asia (39.2 %) or Africa (34.6 %) with the remaining 26.1 % in Latin America. Very few studies (n = 11) combined interventions across more than one domain. The majority of agricultural and nutritional studies were conducted in Africa and Asia, whereas the majority of interventions to improve household air quality were conducted in Latin America. Conclusions It is clear that very little trans-disciplinary research has been done with the majority of studies still being discipline specific. It also appears that certain low and middle income countries seem to focus on domain-specific interventions. The review emphasizes the need to develop holistic, cross-domain intervention packages. Further investigation of the data is being conducted to determine the effectiveness of these interventions and whether interdisciplinary interventions provide greater benefit than those that address single health or community problems.